Enhancing Fiscal Transparency and Reporting in India - Blagrave, Patrick (IMF Working Papers; Working Paper ;, 2020)
Current fiscal transparency and reporting practices in India place it behind most peer G20 economies, implying that policy makers are lacking critical data to ground their fiscal and other economic planning decisions. The increasing use of off-budget financing at the central government level in recent years represents one key example of reduced transparency-we provide estimates of the public sector borrowing requirement and an extended notion of the fiscal deficit, each of which shows a more expansionary stance in recent years than 'headline' deficit figures presented in budget documents. We then investigate the current state of fiscal reporting practices in India and suggest areas for reforms-these include enhanced IT systems, stronger central-local coordination, and a gradual transition to accrual accounting.